Similar but different: intimate partner violence experienced by women and men - Roebuck, Benjamin (Journal of family violence, 2024)
Purpose: Research on intimate partner violence (IPV) is generally focused on female survivors. However, in Canada, about half of all self-reported victims of IPV are men and 1 in 5 calls to police for domestic violence are for male victims. This paper takes a comparative approach to understanding survivors’ experiences of IPV. Methods: Across Canada, 110 female and 45 male survivors of IPV were recruited through media, social media, and listservs for a survey and interviews in 2017. Results: Findings indicate areas of similarity (healthcare needs; difficulty accessing formal support; fear of false accusations) and areas of difference (availability of formal support; types of violence experienced most often; interactions with the justice system). Women and men reported similar types of IPV, with women experiencing higher rates of sexual violence, stalking, and damage to property. Women and men reported similar physical and mental health consequences following IPV. Men were less satisfied than women with the response of the justice system, and both female and male participants encountered gender bias within the justice system. Some women reported being turned away from services that were at their maximum capacity, and men reported difficulty identifying IPV-related services for male survivors. Conclusions: Findings can be used by frontline service providers and the justice system to ensure that services are gender-inclusive and gender-sensitive.